Management fees: determinants and influence of legal limits. Evidence from spanish pension funds - Alda, Mercedes; Ferruz, Luis (Estudios de Economía, 2013)
Pension funds in Spain have become of considerable importance in recent years. In fact, many studies have focused on fund performance and the adverse impact of fees, although little work has been done on analysis of the determinants of fees. Even though fees are restricted by legal limits in many countries, traditional models do not take these limits into account, and results could be biased; therefore, censored models (such as Tobit or CLAD) may provide a better fit. In this work, we study the determinants of management fees in Spanish equity pension funds. We find a better fit in the CLAD model, which provides unbiased and consistent estimators. Additionally, older and larger pension funds charge greater management fees and these fees increase with low volatility. However, fund returns and market returns barely affect such fees.